2020
DOI: 10.1177/1758835920936882
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of PD-1/PD-L1 inhibitors plus nab-paclitaxel for patients with non-small cell lung cancer who have progressed after platinum-based chemotherapy

Abstract: Background: Immunotherapy combined with platinum-based chemotherapy is now the standard first-line treatment for non-small cell lung cancer (NSCLC) patients. However, limited evidence exists to show the efficacy of immunotherapy plus taxanes for patients who have progressed after platinum-based chemotherapy. Methods: The immunotherapy naïve patients with metastatic NSCLC who received anti-PD-1/PD-L1 monoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…In terms of safety, the incidence of AEs was low among patients in this study; grade 3-4 AEs were rare. This suggests that the nab-paclitaxel plus PD-1 inhibitor combination has a favorable safety profile, which is in accordance with the findings of previous studies [24,32]; the safety profile of this combination regimen is significantly better than that of paclitaxel plus gemcitabine for STS therapy [26,33]. This can greatly improve the satisfaction and quality of life of patients undergoing treatment.…”
Section: Table 2 Responses Of Various Histological Subtypes To Treatmentsupporting
confidence: 89%
See 1 more Smart Citation
“…In terms of safety, the incidence of AEs was low among patients in this study; grade 3-4 AEs were rare. This suggests that the nab-paclitaxel plus PD-1 inhibitor combination has a favorable safety profile, which is in accordance with the findings of previous studies [24,32]; the safety profile of this combination regimen is significantly better than that of paclitaxel plus gemcitabine for STS therapy [26,33]. This can greatly improve the satisfaction and quality of life of patients undergoing treatment.…”
Section: Table 2 Responses Of Various Histological Subtypes To Treatmentsupporting
confidence: 89%
“…Nab-paclitaxel is a well-known inducer of immunogenic cell death and has been shown to improve the efficacy of PD-1 inhibitors via the regulation of various immune functions [25,31]. The synergistic effect of nab-paclitaxel combined with a PD-1 inhibitor has been demonstrated [23][24][25]32]. Therefore, the aforementioned combination regimen was selected for the treatment of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, no clinical study has directly compared immunotherapy with immunotherapy + chemotherapy in the second-line treatment of NSCLC. Only a small retrospective study indicated that PD-1/PD-L1 inhibitor + nab-paclitaxel showed significantly longer OS and higher response than PD-1/PD-L1 inhibitor monotherapy in second-line and above therapy for NSCLC [13]. However, the majority of patients in the study received third-line and above therapy (65%), and different types of PD-1/PD-L1 inhibitors were included, which were unreported.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al. ( 133 ) conducted a study on the use of PD-1/PD-L1 inhibitors in separate inhibitors monotherapy and combined with nab-paclitaxel in patients with small cell carcinoma of the lung, found median OS values of 28.6 months and 15.9 months in the nab-paclitaxel and monotherapy groups, respectively. The results reflect the effectiveness of the combination, but this combination still needs to be further explored due to the lack of a control group using chemotherapy alone.…”
Section: Combination With Chemotherapeutic Drugsmentioning
confidence: 99%